Analysis of Customer Feasibility Classification Using the 5C1S Principle to Obtain Hasanah House Financing at BSI KCP Sidoarjo Krian - Yuliana Permata Sari; Arin Setiyowati; Fatkur Huda (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
The high demand for housing among the public has led to a significant increase in the need for home financing, making the role of Islamic financial institutions crucial in providing financing solutions that align with Islamic principles. Bank Syariah Indonesia (BSI), through its Griya Hasanah product, offers home ownership financing that is free from interest (riba) and based on Sharia contracts. However, the growing demand also heightens the potential risk of problematic financing, necessitating a strict and accurate classification of customer eligibility. This study aims to analyze the application of the 5C+1S principles in assessing the eligibility of customers for Griya Hasanah financing at BSI KCP Sidoarjo Krian. The method used is qualitative with a case study approach, employing in-depth interviews with the marketing team and Business Operational Staff (BOSM), along with data triangulation through financing documents and field observations. The findings reveal that the implementation of the 5C+1S principles (Character, Capacity, Capital, Collateral, Condition of Economy, and Sharia Compliance) contributes significantly to reducing the risk of problematic financing. The principles of Character and Capacity carry the highest assessment weight, as they are directly related to the customer's integrity and repayment ability. Meanwhile, the Sharia aspect serves as the main differentiator from conventional financial institutions, ensuring that all financing processes adhere to Islamic values.